Gender Differences and the Role of Social Media in Self-Harm Behavior among Primary School Students - Syahputra, Yuda; Evitarini, Anggia; Sugara, Hendry (Universitas Negeri Padang, 2024)
As technology and social media evolve, children are increasingly susceptible to bad content, including self-harm behaviours. Gender disparities influence the effects experienced, with females being more vulnerable to emotional content and social comparison, whereas boys are more prone to encountering information that promotes hazardous masculine behaviour. This study seeks to investigate variations in self-harm behaviour according to gender and the types of social media often utilised by primary school students in Indonesia. This study is comparative in nature; the sample was chosen by random sampling methods. The study comprised a sample of 372 primary school students, with a gender distribution of 30.2% male and 69.8% female. Data were gathered using the Self-harm Scale, which comprises 24 items in a 4-point response format. The analytical method employs an item response theory framework utilising Rasch model. This study employed descriptive statistics and analysis of variance (Anova) utilising WIinsteps ver. 5.5.0. The findings indicate substantial disparities in self-harm related to gender and the predominant form of social media utilised. This study indicated that the prevailing trend in social media usage among primary school students involves utilising TikTok and WhatsApp for interaction and content sharing.